Van der Waals Multi‐Heterostructures (PN, PIN, and NPN) for Dynamic Rectification in 2D Materials. Issue 24 (8th November 2020) - Aftab, Sikandar; Samiya,; Ul Haq, Hafiz Mansoor; Yousuf, Saqlain; Khan, Muhammad Usman; Ahmed, Zaheer; Aziz, Jamal; Iqbal, Muhammad Waqas; ur Rehman, Atteq; Iqbal, Muhammad Zahir
Abstract: Here, van der Waals multi‐heterojunctions (PN, NP, PIN, and NPN) are fabricated by stacking of MoTe2, hexagonal boron nitride (h‐BN), and MoSe2 nanoflakes using a mechanical‐exfoliation technique where the dynamic rectification is examined. Low‐resistance metal contacts Al/Au and Pt/Au are applied to MoSe2 and MoTe2, respectively, and gate‐dependent rectifying behavior is achieved, with a rectification ratio of up to 10 5 in PN devices. It is found that the performance of the device is enhanced by placing an interfacial layer h‐BN between two opposite layers of 2D materials where the rectification ratio is found to be >10 6 with the ideality factor ≈1.3 in the PIN devices. Also, using the conventional Richardson's plot, the barrier heights of PN and PIN diodes are calculated to be 260 and 490 meV at zero gate bias, respectively. As well, the devices exhibit good performance with a built‐in electric field observed in both PN and PIN diodes, which gives rise to an open‐circuit voltage ( V oc ) and short‐circuit current ( I sc ) under zero external bias. Remarkably, it is found that the performance of the devices also gets better by forming double heterojunction (NPN) layer than PN or NP layers. The device is also tested for a rectification application, and it successfully rectifies an input alternating‐current signal. These findings are important for the development of nano‐ and optoelectronics devices. Abstract : Heterostructures based on 2D materials have immense potential for electronics due to their sharp heterointerfaces. For the applicability of such systems in electronic devices, it is essential to investigate the intrinsic transport in transition‐metal dichalcogenide channel materials, particularly the junction characteristics in multi‐heterostructures.